2022
DOI: 10.14309/ajg.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Center Practices in Liver Transplantation for Alcohol-Associated Liver Disease in the United States

Abstract: INTRODUCTION:Alcohol-related liver disease (ALD) is now the leading indication for liver transplantation (LT) in the United States (US). It remains unclear how centers are managing the medical and psychosocial issues associated with these patients.METHODS:We conducted a web-based survey of LT centers in the United States to identify center-level details on peri-LT management of ALD and related issues.RESULTS:Of the 117 adult LT centers, 100 responses (85.5%) were collected, representing all Organ Procurement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…With ALD now the leading indication for LT in the United States and the ongoing organ supply‐demand mismatch in LT, detection of alcohol use before and after LT has become increasingly important. At this time, most LT programs in the US are not routinely screening for alcohol use in the post‐LT period 24 . The findings from our quality improvement initiative show that when compared directly over a 12‐month period, serum PEth is a better test for both adherence to screening and detection of alcohol use in patients before and after LT. We also noted that, alarmingly, no post‐LT patients completed chemical dependency treatment following detection of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With ALD now the leading indication for LT in the United States and the ongoing organ supply‐demand mismatch in LT, detection of alcohol use before and after LT has become increasingly important. At this time, most LT programs in the US are not routinely screening for alcohol use in the post‐LT period 24 . The findings from our quality improvement initiative show that when compared directly over a 12‐month period, serum PEth is a better test for both adherence to screening and detection of alcohol use in patients before and after LT. We also noted that, alarmingly, no post‐LT patients completed chemical dependency treatment following detection of alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Quality improvement (QI) is an important cornerstone of LT programs as centers seek to continually improve processes of care and patient outcomes 22,23 . A recent national survey showed that most programs do not have alcohol screening protocols in the post‐LT setting despite widespread monitoring in the pre‐LT setting, making this an ideal target for a QI initiative 24 . The aims of this report were therefore to describe the implementation of an alcohol screening and surveillance program in the pre‐ and post‐transplant patients; evaluate center adherence to protocolized testing of two commonly used alcohol biomarkers in pre‐ and post‐LT patients, and to describe likelihood of addressing occult AUD in patients testing positive for alcohol use in the pre‐ and post‐LT settings.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a multidisciplinary approach at transplant centers is needed, as addiction medicine was available at only 2 of the transplant centers in our study (neither embedded within transplant clinics), while 2 centers had access to transplant psychiatry services only. Importantly, educating SNH staff on the present availability of early LT for ALD at more than 70% of transplant centers, including the factors that might be associated with a successful referral as well as implementing more standardized policies around limited sobriety, are important steps to prevent further disparities in access to LT for underinsured, low-income, and racial and ethnic minority patients with ALD.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines and practices surrounding listing and transplantation for ALD are institution specific. A 2015 survey by Hasanin et al found that only 27% of centers provided transplants for patients with severe ALD; this number increased to 51% in a 2018 study by Bangaru et al and further to 85% in a 2021 survey by Lim et al [11][12][13] Throughout the COVID-19 pandemic, there has also been an increase in reported episodes of harmful drinking, alcohol-related hospital admissions, and listing for ALD, with severe ALD accounting for a large number of these waitlist additions. [14][15][16][17] As the pandemic-fueled rise in ALD-related LT continues and ELT for severe ALD has become more widely adopted across the United States, [14][15][16][17] continued examination of the practices of transplant centers and attitudes of transplant providers is a key step in shaping a national consensus that determines the management of patients receiving this therapy.…”
mentioning
confidence: 98%
“…The guidelines and practices surrounding listing and transplantation for ALD are institution specific. A 2015 survey by Hasanin et al found that only 27% of centers provided transplants for patients with severe ALD; this number increased to 51% in a 2018 study by Bangaru et al and further to 85% in a 2021 survey by Lim et al 11–13 Throughout the COVID-19 pandemic, there has also been an increase in reported episodes of harmful drinking, alcohol-related hospital admissions, and listing for ALD, with severe ALD accounting for a large number of these waitlist additions. 14–17…”
mentioning
confidence: 99%